Employee Professionality in the Bureau General Planning and Budget Polda Gorontalo - Widya Kurniati Mohi; Apris Ara Tilome; Fitri D Mohune (Borong Newinera Publisher, 2023)
This study aims to determine the Professionality of Employees in the General Planning and Budget Bureau of the Gorontalo Regional Police. The research method uses a qualitative type. The results showed that the professionalism of employees in the General Planning and Budget Bureau of the Gorontalo Regional Police was not optimal. This can be seen from the 3 (three) indicators used as research benchmarks, only one indicator is considered fulfilled, namely the response indicator indicated by the speed of employees in providing services to line work units related to socialization requests, supervision and budget allocations. The other two indicators, namely the creativity indicator and the innovation indicator, are considered to have not been fulfilled, this is because some employees or personnel do not have the authority to carry out an innovation because they do not have the qualifications and competencies in their position so that so far the existing employees or personnel only work according to regulations. existing or in other words work normatively.